BUSINESS STRATEGY OF MUSLIM FAMILY BUSINESSES DURING PANDEMIC COVID-19 - SHEEMA HASEENA ARMINA; MUFTI AFIF; MUHAMMAD AGUS SETIAWAN (Universitas Islam Negeri Imam Bonjol Padang, 2023)
The pandemic covid-19 engulfed the entire world and influenced all business especially in Micro, Small and Medium Enterprise. This clarification leaves a business strategy issue that needs to be a question whether any changes or standstill. This study aims to analyze business strategy of a family business that sells typical food in a region namely sate Ayam Setono village Ponorogo. The using method is qualitative with case study exploratory approach by observation, interview and documentation. This study found that the business strategy has not changed much in this food family business during pandemic covid-19. The fear and anxiety that most people feel about sophistication of the government’s pandemic policy has an effect on the overall operation of the company, just digitization does not match seller’s capabilities while simultaneously attempting to preserve the qualities of this business. Attempts to change this strategy digitally have previously been made, but little has changed, so not every business impacted by covid-19 will adapt its business strategy online, because the Setono Ponorogo chicken satay company is one way of maintaining its features directly in society knowledge.